Peran Pendidikan Karakter Untuk Generasi Muda Berdaya Tahan dalam Mendukung Ketahanan Nasional: Analisis Holistik - Muhammad Raffin Althafullayya (Journal Education Innovation (JEI), 2024)
Character education plays a central role in shaping the younger generation as the backbone of the nation's future, emphasizing values such as responsibility, honesty, patriotism, leadership, tolerance, and discipline. Young people with strong character are expected to bring energy, vision, and innovation to strengthen national resilience, encompassing economic, social, cultural, and technological aspects. Character education establishes a solid foundation for the personality of the younger generation by emphasizing national values such as integrity, responsibility, and a spirit of mutual cooperation. This is expected to strengthen the foundation of national security and stability through an understanding of national values connected to the roots and identity of the nation. Moreover, character education also plays a role in shaping responsible leadership among the younger generation. They are expected to be agents of change who are wise, collaborate effectively, and lead with integrity, especially in the context of national resilience. The importance of character education is not only related to the formation of individuals who are personally good but also creates a strong foundation for the active role of the younger generation in maintaining national resilience. Integration into the curriculum, involvement of parents and the community, non-formal education, and experience-based approaches are strategies to achieve more integrated and holistic character education. Research methods that can be employed involve qualitative approaches and literature reviews to delve into the analysis of the concepts of character education, the role of the younger generation, and national resilience. Thus, it is expected that character education can be an effective instrument in shaping the younger generation as a positive force in addressing the complex dynamics of society and the nation.